Financing Patterns of European SMEs Revisited: An Updated Empirical Taxonomy and Determinants of SME Financing Clusters - Christian Masiak; Alexandra Moritz; Frank Lang (European Investment Fund (EIF), 2017)
This EIF Working Paper investigates financing patterns of European SMEs by looking at a large number of different financing instruments and their complementary and substitutive effects, using the SAFE dataset collected in 2015. We develop an empirical taxonomy of SME financing patterns in Europe, applying cluster analyses. In order to investigate the cluster stability over time, we replicate an approach by Moritz et al. (2016)2, who used the SAFE data from 2013. In addition, we extend that study by looking at the role of the country-specific macroeconomic and institutional environment for the financings patterns of SMEs. Our results confirm the results of Moritz et al. (2016) and show that European SME financing is not homogenous, but that different financing patterns exist. Our cluster analysis identifies seven distinct SME financing types based on the financing instruments used: mixed-financed SMEs with focus on other loans, mixed-financed SMEs with focus on retained earnings or sale of assets, state-subsidised SMEs, debt-financed SMEs, trade-financed SMEs, asset-based financed SMEs, and internally-financed SMEs. Moreover, the SME financing types can be profiled according to their firm-, product-, industry-, and country-specific characteristics. Our findings can support policy makers in assessing the impact of changes in policy measures for SME financing.
Keywords: G32; G21; G24; G18; 330; EIF; European SME financing; financing patterns; empirical taxonomy; cluster analysis